Situating Kalhana and his Chronicle Rajatarangini. - Hangloo, Rattan Lal (ICFAI Journal of History & Culture, 2009)
History is re-written in every age but historians have to guard not only against the prejudices of the past but also of the future otherwise their work would be untranslatable in troubled times. This paper has grown out of an interest in Kalhana's Rajatarangini which has not received adequate attention in Indian historiography. Kalhana is one of the foremost historians of early Kashmir and one of the most original scholars in this field. His method, however, does not only fit the familiar moulds of social, economic, political and cultural history but his writing also corresponds to our history of ideas and over laps with what has recently become known as the history of mentalities. This paper is not concerned with the details of looting of Kashmir by Damaras or with the abilities of Kings such as Lalitaditya as illustrated by Kalhana. But it indicates how necessary interpreting the Rajatarangini is as a source text as the evidence of a personal stand point, which has acquired a lasting significance from the individuality of the author, uniqueness of the historical situation and specificity of region and time. The principle subject is not the historical reality of events and state of affairs recorded by Rajatarangini; what appeals the reality of the mental activity manifested in this chronicle which also shows how Kalhana's account of complex social economic and political processes and patterns in Kashmir interacted with the wider world.